A Day Late and a Dollar Short: Examining Perceptions of Which Exonerees Deserve Compensation - Olson, Alexandra; Henderson, Kelsey S.; Harmon, Mark G.; Carey, Christopher (The Wrongful Conviction Law Review, 2023)
Many exonerees do not receive compensation from the state after they are released (43%) because most states have exclusionary laws that bar exonerees from receiving compensation (n = 16 states) (Compensation Primer, 2022). This study examined public perceptions of exoneree compensation, exclusionary laws and addressed the broader question of who deserves compensation (according to community members). Online participants (n = 225) read an article about a fictional exoneree who either pleaded guilty or was convicted by a jury trial and who either did or did not have a subsequent conviction. An exoneree with a subsequent conviction was perceived as less deserving of financial compensation (roughly $8,000 less annually) and less deserving of support services. It was rated less positively than an exoneree who did not have a subsequent conviction. No differences were found between an exoneree who pleaded guilty and an exoneree who was convicted by a jury trial, demonstrating little impact of this common exclusionary rule on community members’ perceptions and decisions. Overall, participants overwhelmingly supported exoneree compensation (only 6.7% disagreed). However, there are caveats. Community members are less supportive of compensating exonerees who have subsequent involvement with the justice system. These results illustrate possible biases the public has against an already marginalized population that has experienced a miscarriage of justice. Because public opinion can affect policy change, these results significantly affect state exclusionary rules and exoneree compensation policies.